Burning Bright Play Still - Broadhurst Theater:::Creator::::::::::::
Mordeen (Barbara Bel Geddes) with Joe Saul (Kent Smith) in the play adaptation of John steinbeck's Novella. This show closed after thirteen performances at the Broadhurst Theatre in New York. Digital copy only. No hard copy.